Pattern of Anemia in Patients with Heart Failure in Ischemic Heart Disease - Dhungel, Sachin; Gautam, Samir; K.C, Bishal; Khan, Mazhar; Shakya, Abhishesh; Bhattrai, Prayantna; Yadav, Manisha; Khadka, Bishal; Shrestha, Munal (Journal of National Heart and Lung Society Nepal, 2024)
Background: Anemia is common health problem encountered in patients with heart failure which in turn is is one of the common presenting feature of ischemic heart disease.This study aims to study the patterns and types of anemia in patients admitted with heart failurein ischemic heart disease. Methods: A cross sectional hospital based study for one year in eligible patients as ischemic heart disease in clinical heart failure. Blood parameters especially RBC indices, biochemical parameters including iron profile, serum ferritin, vitamin B12,folic acid were studied. Results: Out of 77 patients with mean age 67±7 years, anemia was common in female (63.6%) and elderly (66.2%). Other most common precipitants of heart failure in anemia were recent MI (